In-house resource efficiency improvements supplementing the end of pipe treatments in textile SMEs under a circular economy fashion - Kumar, Love; Kamil, Ifrah; Ahmad, Muhammad; Naqvi, Sohail Ali; Deitch, Matthew J.; Amjad, Arjmand Qayyum; Kumar, Avinash; Basheer, Sarosh; Arshad, Masood; Sassanelli, Claudio (Frontiers in Environmental Science, 2022)
The choice of cleaner production practices within the supply chain can improve the textile industry's environmental, financial, and operational advantages. The objective of this study is to evaluate Smart Environmental Management Practices (SEMPs) for minimizing the pollution load (energy waste, water consumption, wastewater generation, and chemical waste) within the supply chain in five textile production units of Lahore, Faisalabad (Punjab), and Karachi (Sindh) in Pakistan, and to assist and get comprehensive knowledge on resource-saving through cleaner production techniques. A multi-criteria decision-making method was used to identify the possibilities and use for cleaner production and SEMPs. A total of 36 SEMPs have been recorded with three benchmarking levels based on investment and business priority: i) Low/No Cost High Return, ii) High-Cost High Return, and iii) Medium Cost Medium Return. After an initial assessment, SEMPs were implemented, and post-assessments were conducted after a gap of months. It was found that about 1.3 million m3 of water was saved which made 21% of the total water consumption. Moreover, 34 600 tons of chemical and 1 441 500 kW h energy were also saved. This resource-saving also helped industries save 0.792 million USD. Using the SEMPs proposed in this article, the annual GHG emission was significantly reduced for industries where the potential varied from 200 - 8 500 tons of CO2 for different industries.